Porcine circovirus structure and replication: a minireview - Weingartl, Hana M. (Agricultura Scientia, 2020)
Porcine circoviruses (PCV) are nonenveloped, and have covalently linked circular single stranded (ss) DNA genome. They are the smallest animal viruses capable of independent replication. Circoviruses are thought to use a rolling circle strategy for DNA replication, a unique feature among animal viruses. Three major viral proteins were identified in PCV infected cells: Rep and Rep', involved in genome replication, and the capsid protein. Porcine circoviruses have to rely heavily on the host cell machinery for their replication. Although PCV1 was described in 1974, interest in these viruses has significantly increased only in late nineties, when PCV2 was discovered and linked to several porcine disorders. Our knowledge of porcine circoviruses replication and the basis for their pathogenesis is still very limited.
Keywords: porcine circovirus; viral proteins; porcine disordes